Technique for Arthroscopic Transtibial Medial Meniscus Posterior Root Repair - Danny Lynch BS; Robert A. Duerr MD (SAGE Publishing, 2022)
Background: Medial meniscus posterior root tears (MMPRT) can lead to significant pain, functional limitations, and osteoarthritis (OA). Biomechanically, MMPRT has been shown to be equivalent to total meniscectomy in terms of peak contact pressure in the medial compartment. Transtibial repair of a meniscus root tear has also been shown to restore hoop stresses and reduced peak contact pressure to the normal intact state. Clinically, root repair was shown to reduce rates of OA progression and need for total knee arthroplasty when compared with nonoperative treatment or partial meniscectomy for MMPRT. Indications: Medial meniscus posterior root repair is indicated in patients with a symptomatic MMPRT who are appropriate surgical candidates: age ≤65 years, body mass index ≤40 kg/m 2 , <5° varus alignment, no more than Kellgren-Lawrence grade 2 changes, and willing and able to undergo the demanding postoperative rehabilitation program. Technique Description: This surgical technique video demonstrates our preferred technique for arthroscopic transtibial medial meniscus posterior root repair using a case example in a commonly encountered patient. The repair is completed using a 3 simple suture triangle configuration with 2 tibial tunnels to create a broad footprint for healing. Results: There are a number of case series and comparative studies published with good clinical outcomes using similar transtibial medial meniscus posterior root repair techniques. In short-term follow-up of 18 patients at a mean of 10.5 months post-operatively, we have demonstrated improvements in pain and functional status with a 16.7% clinical failure rate and 11% rate of conversion to arthroplasty. Discussion: In this surgical technique video, we review the anatomy of the native medial meniscus posterior root and the biomechanical and clinical consequences of a MMPRT. We highlight important technique pearls and pitfalls to avoid failures and complications during the surgical demonstration. Finally, we review postoperative rehabilitation guidelines and clinical outcomes within the existing literature. In patients with MMPRT, transtibial repair provides a safe and reliable technique to achieve healing of the medial meniscus posterior root and return patients to full activities with reduced risk of OA progression.